Pengaruh Pemberian Minyak Cumi Pada Pakan Terhadap Respon Makan Ikan Kerapu Cantang (Epinephelus fuscoguttatus x Epinephelus lanceolatus) - Ricko Rionaldo; Tri Yulianto; Henky Irawan (Intek Akuakultur, 2021)
This study aims to determine the dose of squid oil attractant to increase the feeding response of grouper Epinephelus fuscoguttatus x Epinephelus lanceolatus. This research was conducted in March 2020 at the Fish Seed Center, Pengujan Village, Bintan Regency, Riau Islands Province. The method used was an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications, where treatment K: (Megami feed without attractants), treatment A: (Megami feed + 6 ml/kg of squid oil), treatment B : (Megami feed + 9 ml/kg squid oil), treatment C: (Megami feed + 12 ml/kg squid oil). Data analysis with Analysis of variance (ANOVA) and Duncan's continued test, showed that the fastest response of fish to feed was at a dose of 12 ml/kg or treatment C was the fastest treatment, the results obtained were at the level of feed consumption (99.23 Â± 0.67%) and survival rate (100 Â± 0.00%).